The Effect of Body Region on Hair Cortisol Concentration in Common Marmosets (Callithrix jacchus) - Bartling-John, Evelyn E (Comp Med, 2021)
Common marmosets (Callithrix jacchus) are a valuable research model for the study of neuroscience and the biologic impact of aging due to their adaptivity, physiologic characteristics, and ease of handling for experimental manipulations. Quantification of cortisol in hair provides a noninvasive, retrospective biomarker of hypothalamics-pituitary-adrenal (HPA) axis activity and information on animal wellbeing, including responses to environmental and social stimuli. To obtain valid and reliable measurements of long-term HPA activity, we investigated the variability of cortisol concentration in the hair depending on the body region of marmosets. Hair was collected from the back and tail of 9 adult common marmosets during annual health screenings (male n = 3; female n = 6) and these samples were analyzed for cortisol via methanol extraction and enzyme immunoassay. We found that hair cortisol concentration differed between the tail and back regions, with the tail samples having a significantly higher cortisol concentration. These results indicate intraindividual and interindividual comparisons of hair cortisol concentration should use hair obtained from the same body region in marmosets.